KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AHLAK PESERTA DIDIK DI SD NEGERI 030326 TIGALAMA KECAMATAN PEGAGAN HILIR KABUPATEN DAIRI PROVINSI SUMATRA UTARA - Simanjorang, Junyedi; Uliyah, Taqwatul; Fitria, Norma (UNISAN JURNAL, 2025)
This study aims to provide an in-depth description of the personal competence of Islamic Religious Education (IRE) teachers in cultivating students’ moral character at SD Negeri 030326 Tigalama, Pegagan Hilir District, Dairi Regency, North Sumatra Province. Personal competence, as one of the core components of teacher professionalism, plays a crucial role in shaping students’ moral behavior, particularly at the elementary level where character development is closely linked to daily habits and modeling. Therefore, this research seeks to explore how IRE teachers demonstrate emotional stability, maturity, moral authority, integrity, and exemplary conduct both inside and outside the classroom as part of the moral education process. This research employs a descriptive qualitative approach, focusing on the real experiences of teachers, students, and the school environment. Data were collected through in-depth classroom observations, interviews with IRE teachers, the principal, and selected students, as well as documentation of religious activities and character-building programs. Data analysis followed the stages of reduction, display, and conclusion drawing conducted continuously. The study highlights various forms of teacher modeling in instilling values such as discipline, responsibility, honesty, politeness, and social awareness that form the foundation of moral character (akhlaq). The findings indicate that the personal competence of IRE teachers is strongly reflected through consistent exemplary behavior, polite communication, emotional self-control, and the ability to deliver persuasive and constructive advice. IRE teachers play a dual role not only as transmitters of religious knowledge but also as moral role models whom students look up to in their daily lives. In addition, moral cultivation is reinforced through routine religious activities such as prayers, Qur’anic recitation, daily greetings, and school-wide behavioral habits. A supportive school environment, collaboration with homeroom teachers and parents, as well as a jointly established religious atmosphere contribute significantly to the effectiveness of moral development. Thus, this study highlights that the personal competence of IRE teachers is a key determinant of effective and sustainable moral education for students. Keywords: Personality Competence, Islamic Education Teachers, Student Morals, Character Building, Elementary Schools